Palabras, mejor de una en una: los niños con dislexia ante la lectura de palabras presentadas simultáneamente - Suárez-Coalla, Paz; Álvarez-Cañizo, Marta; Jiménez, Sebastián (Revista de Investigación en Logopedia, 2022)
Different studies have reported that proficient readers benefit from the simultaneous presentation of words during reading. On the other hand, the availability of orthographic representations of words appear to facilitate the initiation of phonological encoding of the contiguous word, which would be triggered during the articulation process of the target word. However, this advantage might not be evident in children with dyslexia, given their poor reading competence. The purpose of this study was to investigate whether children with dyslexia benefit from the simultaneous presentation of written words and whether this is dependent on the characteristics of the stimuli. For this aim, children with and without dyslexia participated in two reading tasks. In the first task, words, manipulated in frequency and length, were displayed in isolation, while the second task involved lists of three words, in which the frequency and length of the third word were manipulated. The results showed reading difficulties in participants with dyslexia, with poorer reading performance than the control group in both tasks. On the other hand, both groups demonstrated an advantage of simultaneous word presentation, with shorter pre-word articulation times in simultaneous presentation than in single word presentation. However, this benefit did not occur in articulation times and reading accuracy in children with dyslexia, especially for long and infrequent words, suggesting that dyslexic children do not reach the same level of preprocessing as children in the control group.